Journalistic autonomy : the genealogy of a concept - Örnebring, Henrik; Karlsson, Michael, 1970- (Journalism in perspective: continuities and disruptions., 2022)
"Journalists around the world agree that autonomy is central to their work, but what exactly is it journalists should be autonomous from, and for what should they use this autonomy? This book traces the idea of journalistic autonomy from the 17th century to our contemporary digital age"--